The biology of Palexorista laxa (Curran) (Diptera : Tachinidae) : an internal larval parasitoid of Heliothis armigera (Hübner) Lepidoptera : Noctuidae) - Van Heerden, Desireé (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1993)
The Tachinid fly, Palexorista laxa (Curran) is an important parasitoid of Heliothis armigera (Hubner) in Africa and India. The biological characteristics of the parasitoid were studied with an emphasis on its host instar preference, host range, seasonality and percentage parasitism. The developmental stages were also studied and described. A high host mortality (48%-100%) due to parasite attack occurred when small larvae were parasitised (2nd & 3rd instars). A preference for the 4th and 5th host instars was shown by the flies. P. laxa was found to be a non-specific parasitoid and parasitised a number of lepidopterous larvae in the laboratory including Busseola fusca (Fuller), Chilo partellus (Swinhoe) and Eldana saccharina Walker, but preferred Ii. armigera. The percentage parasitism on H. armigera in the field was variable peaking at 48% in 1988/89. Of the various parasitoids recorded from H. armigera on sunflower P. laxa was by far the most abundant. Mating occurred immediately after emergence with the males emerging a day earlier than the females. Males were capable of multiple matings whereas females mated only once in a lifetime. P. laxa females produced incubated macrotype eggs which hatched almost immediately after oviposition. The duration of development of the incubated egg and larval stage was 6,7 days, the pupa 10,4 days for females and 9,4 days for males, and the adult lived up to 50 days at 25°C. A reduction in pupal weight, an increase in the duration of the pupal stage and higher pupal mortality accompanied an increase in density of parasitoids per host. A linear relationship was shown between adult mass and number of ovarioles and eggs in P. laxa females. The oviposition period was 26,9 days with a high variation in daily progeny production. The total fertility per female was 126,3 puparia. "Inexperienced" females deposited incubated eggs on all parts of the host body while "experienced" females confined oviposition to the head and thorax. P. laxa females did not discriminate between previously parasitised and non-parasitised hosts. The effect of temperature on larval and pupal survival and development time was studied at 20°, 22°, 25°, 28°and 30°C. As expected, duration of development decreased with an increase in temperature, and there was a reduction in mortality.
Keywords: Tachinidae; Helicoverpa armigera -- Parasites -- Life cycles; Noctuidae